Use of macadamia nutshell in the production of eucalyptus salign particleboards - Ferreira, Bruno Santos [UNESP]; de Campos, Cristiane Inácio [UNESP]; Gonçalves, Marcos Tadeu Tibúrcio [UNESP] (Trans Tech Publications, 2014)
Alternative raw materials have been studied for the total or partial replacement of wood in wood panels, in order to decrease the use of wood and to recovery waste. The present study tested the influence on the physico-mechanical properties of the panels produced with particles of Eucalyptus saligna and macadamia nutshell. For those were produced panels in proportions of 0%, 30%, 60% and 100% with respect to the macadamia nutshells. With the obtained results it was noticed that the increasing of the nutshell proportion led to a decrease in the dimensional stability, internal bonding and bending strength. These results were primarily due to the geometry of the particles of macadamia nutshell, besides being thicker, not allowing a good interaction between them and the adhesive, they were shorter, reducing the bending strength.
Keywords: Particleboard; Physic-mechanical properties; Waste recovery